2022
DOI: 10.1002/cac2.12381
|View full text |Cite
|
Sign up to set email alerts
|

Detection of piRNA‐54265 in human serum: evidence and significance

Abstract: Dear Editor,An increasing number of studies have shown that PIWIinteracting RNAs (piRNAs) are aberrantly expressed in many types of human cancer and involved in regulating the malignant progression, piRNAs would be expected to serve as molecular biomarkers for cancer screening and early diagnosis.In a previous study, we have identified the presence of piRNA-54265 in human serum [1]. Further research has demonstrated that it is a promising and specific blood molecular marker for colorectal cancer (CRC) [2]. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Note that a recent report suggests that piRNA-54265, detected in the serum, is likely a full-length small nucleolar RNA, SNORD57 [169]. To clarify this important issue, Mai et al [170] further verified the identity of piRNA-54265 in human serum samples and confirmed their earlier findings.…”
Section: Circulating Piwi-interacting and Small Nucleolar Rnasmentioning
confidence: 75%
“…Note that a recent report suggests that piRNA-54265, detected in the serum, is likely a full-length small nucleolar RNA, SNORD57 [169]. To clarify this important issue, Mai et al [170] further verified the identity of piRNA-54265 in human serum samples and confirmed their earlier findings.…”
Section: Circulating Piwi-interacting and Small Nucleolar Rnasmentioning
confidence: 75%
“…Tosar et al suggested that the results of these studies were incorrectly interpreted as small nucleolar RNA SNORD57 [57]. However, the authors of mentioned studies proved that it was indeed piR-54265 and not SNORD57 [58].…”
Section: Colorectal Cancermentioning
confidence: 99%